Cytotoxicity and polyphenol diversity in selected parts of Mangifera pajang and Artocarpus odoratissimus fruits. - Abu Bakar, Mohd Fadzelly; Mohamed, Maryati; Rahmat, Asmah; Burr, Steven A.; Fry, Jeffrey R. (Emerald Group Publishing, 2010)
Purpose Research on cancer chemopreventive properties of fruits has increased in recent years. Polyphenols have been suggested to exert such effects. The purpose of this paper is to determine the cytotoxic activity of Mangifera pajang (bambangan) and Artocarpus odoratissimus (tarap) crude extracts against selected cancer cell lines (i.e. ovarian, liver and colon cancer) and to compare the amount of selected polyphenols (phenolic acids, flavanones, flavonols and flavones) in the kernel, peel and flesh of M. pajang; and the seed and flesh of A. odoratissimus.